2021
DOI: 10.3233/jnd-210630
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin Neuropathy: Predictive Values of Skin Biopsy, QST and Nerve Conduction

Abstract: Background: Oxaliplatin-induced peripheral neuropathy negatively affects the quality of life for patients with gastrointestinal cancers and may cause neuropathic pain. Measures of peripheral nerve structure or function, such as intraepidermal nerve fiber density (IENFD) during treatment could reduce neuropathy severity through individualized dose reduction. Objective: The aim was to evaluate the predictive values of IENFD, quantitative sensory testing (QST), and nerve conduction studies (NCS) for significant n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [17,41,[58][59][60][61][62][63][64]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Nerve Conduction Studies (Ncs) and Electromyographymentioning
confidence: 73%
See 4 more Smart Citations
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [17,41,[58][59][60][61][62][63][64]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Nerve Conduction Studies (Ncs) and Electromyographymentioning
confidence: 73%
“…The assessment of sural nerve instead dorsal sural (Figure 2), and the size of the study could underlie these negative findings. Long-term longitudinal neurophysiological assessments of OXA-treated patients have revealed a significant recovery of the SNAPs in sensory nerves in some studies [58,63,71] but not in other studies [59,61]. The length of follow-up observation may explain these differences.…”
Section: Nerve Conduction Studies (Ncs) and Electromyographymentioning
confidence: 94%
See 3 more Smart Citations